Eye tracking in a teaching context: comparative study of the professional vision of university supervisor trainers and pre-service teachers in initial training for secondary education in French-speaking Belgium - Duvivier, Valérie; Derobertmasure, Antoine; Demeuse, Marc (Frontiers in Education, 2024)
This study explores the visual strategies of University Supervisor Trainers (UST) for teachers (Upper Secondary Education Teaching Certification -Agrégation de l'Enseignement Secondaire Supérieur (AESS)) in French-speaking Belgium and the pre-service teachers (PT) they train. It aims to understand how these two groups observe a teaching situation, on video, using an eye-tracking device. The video shows the start of a geography lesson given by a trainee in a primary school class. Three research questions were formulated, examining a) the actor observed (the trainee, the pupil working groups and 4 pupil profiles present in the scene), b) the visual strategies used to access these actors and c) the visual itineraries when a planning error by the trainee is presented on the screen. To answer, we chose to carry out an analysis based on oculometric indicators (fixing, visit and first view). The results show that UST and PT focus their attention on the same groups of students. However, they do not do so in the same way. UST adopt visual strategies that are distinct from those of PT, thus aligning their approaches with those of expert teachers in other studies using eye tracking. Within these strategies, we highlight two important points: a) the emergence of dynamic and floating visual strategies in the UST, characterised by more frequent revisits (significantly validated) and fixations of shorter duration than in PT; and b) less fixation of UST in observing students who are very active in class compared to PT. Finally, the specific analysis of the UST gaze itineraries at the time of the trainee's planning error reflected both common elements (e.g. teaching tools) and divergent elements (e.g. checking pupils).1 Future upper secondary teachers are considered to be pre-service teachers and are therefore referred to in this article by the acronym 'PT' (for 'Pre-service Teacher').